2016
DOI: 10.3389/fpsyg.2016.01949
|View full text |Cite
|
Sign up to set email alerts
|

Distraction by Novel and Pitch-Deviant Sounds in Children

Abstract: The control of attention is an important part of our executive functions and enables us to focus on relevant information and to ignore irrelevant information. The ability to shield against distraction by task-irrelevant sounds is suggested to mature during school age. The present study investigated the developmental time course of distraction in three groups of children aged 7–10 years. Two different types of distractor sounds that have been frequently used in auditory attention research—novel environmental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…We analyzed two types of rapid orienting responses: the 'ocular freezing' (MSI) response (Engbert and Kliegl, 2003;Hafed and Clark, 2002;Hafed and Ignashchenkova, 2013;Rolfs et al, 2008) and the pupil dilation response (PDR; Wang et al, 2017;Wang and Munoz, 2015). Both have been shown to systematically vary with visual salience (Bonneh et al, 2014;Rolfs et al, 2008;Wang et al, 2017 and have also been demonstrated to be evoked by auditory stimuli (Liao et al, 2016;Rolfs et al, 2008Rolfs et al, , 2005Munoz, 2015, 2014;Wetzel et al, 2016), consistent with the notion that they reflect the operation of modality-general interrupt process.…”
Section: (4) Crowd-sourced Salience Correlates With Objective Measurementioning
confidence: 68%
“…We analyzed two types of rapid orienting responses: the 'ocular freezing' (MSI) response (Engbert and Kliegl, 2003;Hafed and Clark, 2002;Hafed and Ignashchenkova, 2013;Rolfs et al, 2008) and the pupil dilation response (PDR; Wang et al, 2017;Wang and Munoz, 2015). Both have been shown to systematically vary with visual salience (Bonneh et al, 2014;Rolfs et al, 2008;Wang et al, 2017 and have also been demonstrated to be evoked by auditory stimuli (Liao et al, 2016;Rolfs et al, 2008Rolfs et al, , 2005Munoz, 2015, 2014;Wetzel et al, 2016), consistent with the notion that they reflect the operation of modality-general interrupt process.…”
Section: (4) Crowd-sourced Salience Correlates With Objective Measurementioning
confidence: 68%
“…In an auditory‐visual distraction study, 7‐ to 10‐year‐old children showed larger distraction effects in response to novel sounds than 11‐ to 13‐year‐old children (Gumenyuk et al., ). The development of attention control during the period of 7–10 years was specified in a recent similar auditory‐visual distraction study that reported decreased distraction effects with age in three groups of children aged 7, 8, and 9 to 10 years (Wetzel, Schröger, et al., ). In line with this ongoing maturation of attention control abilities during middle childhood, we observed reduced distraction effect between the group of the 6‐year‐old children and the group of 9‐ to 10‐year‐old children.…”
Section: Discussionmentioning
confidence: 99%
“…This is frequently reflected by prolonged reaction times (RTs) in distractor trials relative to standard trials in an auditory or visual categorization task (Escera, Alho, Winkler, & N€ a€ at€ anen, 1998;Schr€ oger & Wolff, 1998). Some developmental studies reported larger distraction effects in younger children compared with older children or adults (Gumenyuk et al, 2001;Wetzel & Schr€ oger, 2007;Wetzel, Schr€ oger, & Widmann, 2016;Wetzel, Widmann, Berti, & Schr€ oger, 2006). In contrast, no increased distraction effects were observed in 9-to 10-year-old children compared with adults (Ruhnau, Wetzel, Widmann, & Schr€ oger, 2010;Ruhnau et al, 2013).…”
mentioning
confidence: 99%
“…In middle childhood, usually during elementary school years, developmental studies reported inconsistent results on attention control. A number of studies presenting a sequence of frequently presented and repeated standard sounds and infrequently presented unexpected novel or deviant sounds reported increased distraction effects in younger than older children in response to novel or deviant sounds in the middle childhood [e.g., 13 15 ]. Immature attention control in children aged 7–10-years was also reported by studies using different approaches, e.g.…”
Section: Introductionmentioning
confidence: 99%